MANAJEMEN REDAKSIONAL RUBRIK ZETIZEN RIAU POS DALAM MENARIK MINAT BACA PADA REMAJA DI KOTA PEKANBARU - Stifani Realdi; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The reform era marked by the rise of the mass media as a means of mass communication and public opinion-forming tool, it helps in human life to exchange ideas, experiences and information in a relatively large volume. The purpose of this study was to investigate the application of management functions are functions of planning, organizing, and monitoring.This study uses qualitative research with descriptive analysis. The research was conducted at Graha Pena 3rd Floor Room Editor Pekanbaru Riau Pos located at Jl. HR Subrantas Km. 10.5 Panam, Ex. Sidomulyo West district. Handsome, Pekanbaru, Riau. Pemelihan infroman done by using purposive.As for the informants of this study is the editorial director of Riau Pos, coordinator rubric Zetizen Riau Pos, two crew Zetizen Riau Pos and loyal readers Zetizen Riau Pos. Data collection techniques used for conducting research is by observation, interview and documentation. While the validity of the data that researchers use is extended participation, triangulation as well as the adequacy of reference.The results showed that, in describing the application of the editorial management functions Riau Pos Zetizen in attracting interest in reading among adolescents in the first Pekanbaru City planning, planning is divided into two groups: strategic planning and operational planning. Meanwhile, the second management function is the organization that is the organizational structure and job description. Then the third management functions namely mobilization, mobilization divided into three groups: news reporting, editing and writing news. Last management functions that control the shape of the oversight conducted Zetizen rubric Riau Pos namely evaluation and feedback.